2009
DOI: 10.1099/vir.0.007914-0
|View full text |Cite
|
Sign up to set email alerts
|

A role for autophagolysosomes in dengue virus 3 production in HepG2 cells

Abstract: We have recently proposed that amphisomes act as a site for translation and replication of dengue virus (DENV)-2 and that DENV-2 entry and replication are linked through an ongoing association with membranes of an endosomal-autophagosomal lineage. In this report, we present the results of an investigation into the interaction between DENV-3 and the autophagy machinery. Critically, treatment with the lysosomal fusion inhibitor L-asparagine differentiated the interaction of DENV-3 from that of DENV-2. Inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
99
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 47 publications
7
99
0
Order By: Relevance
“…Autolysosomes are reported as potential DENV replication sites, at least for DENV serotype 3 (6). Notably, that study revealed a similar increase in LC3-II levels upon DENV-3 infection.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Autolysosomes are reported as potential DENV replication sites, at least for DENV serotype 3 (6). Notably, that study revealed a similar increase in LC3-II levels upon DENV-3 infection.…”
Section: Discussionsupporting
confidence: 63%
“…Here, we report findings that suggest a biphasic response of autophagy to DENV infection, where DENV infection initially activates and then later on inhibits autophagy. Although it has been reported by several groups that multiple components of the autophagy pathway are required for DENV replication (4,6,7,(27)(28)(29), we demonstrate here that DENV activates autophagy only during the early infection stage. Moreover, we established that, by 24 h after infection with the NGC strain, autophagosome formation is inhibited and lysosomal degradation of AVs is reduced.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, inhibition of autophagosome degradation might enhance virus particle exocytosis 58 . Furthermore, the stabilization of autophagosome membranes for viral replication has been proposed for other RNA viruses, like the flaviviruses hepatitic C virus (HCV) and dengue virus [59][60][61][62][63] . Moreover, even RNA viruses that do not use autophagosomal membranes for their replication, seem to benefit from inhibition of autophagosome degradation for their release of infectious viruses from infected cells 64 .…”
Section: Viral Evasion From Macroautophagymentioning
confidence: 99%